Pawns - Roberts, Willo Davis (New York : Atheneum Books for Young Readers, 1998)
After her mother's death and her father's suicide, fourteen-year-old Teddi finds some stability when she moves in with Mamie, her good-hearted nextdoor neighbor-- until the arrival of a woman claiming to be the pregnant wife of Mamie's son who recently died in a plane crash.
"A Jean Karl book."
770
Keywords: Orphans -- Fiction; Death -- Fiction; Swindlers and swindling -- Fiction; Mystery and detective stories